Hambatan Komunikasi Mamak Dengan Kemenakan Melalui Media Sosial Whatsapp - Claudia, Rany; Setiawati, Ida Agus (Jurnal Empirika, 2025)
Mamak in matrilineal societies in Minangkabau hold a prominent position as the person responsible for the main family and their family of origin, including their nephews and nieces. This role is not limited to that of an uncle, but also as a leader and guardian of family heirlooms. However, this role cannot be optimally performed by mamak who live far from their homeland. Social media has become an alternative for mamak to maintain communication, preserve relationships, foster family traditions, and provide attention to their nieces and nephews. However, virtual communication poses obstacles for mamak to perform their roles optimally. This study uses descriptive qualitative research. The technique for determining informants is purposive sampling with 7 informants who are migrants. The results of the study show that the obstacles found are ineffective emotional closeness and interaction with nieces and nephews, adaptation from conventional to virtual communication makes it difficult for mamak to use social media, internet networks that are sometimes unstable, and limited internet quota costs. In this virtual communication, these obstacles affect social symbols and emotional closeness that can be interpreted and translated in direct interactions to maintain family relationships with nieces and nephews.